Myocardial perfusion/metabolism mismatch and ventricular arrhythmias in the chronic post infarction state - Krause, B. J.; Poeppel, T. D.; Reinhardt, M.; Vester, E.-G.; Yong, M.; Mau, J.; Strauer, B.-E.; Vosberg, H.; Müller, H.-W. (Nuklearmedizin - NuclearMedicine, 2005)
Aim: Ventricular arrhythmias have been shown to originate in the myocardial peri-infarct region due to irregular heterotopic conduction. Hypoperfused but viable myocardium is often localised in those areas and may be involved in the pathogenesis of arrhythmias. We tested the hypothesis that these myocardial perfusion/metabolism mismatches (MM) are significantly associated with ventricular arrhythmias in the chronic post infarction state. Patients, methods: 47 post infarction patients were included in the study. 33 suffered from ventricular arrhythmia whereas 14 did not. All patients underwent 99mTc tetrofosmin SPECT and 18F-FDG PET. A region-of-interest(ROI)-analysis was used to assess viable myocardium based on predefined MM-criteria. Univariate analyses as well as a logistic regression model for the multivariate analysis were carried out. Results: 94% of the arrhythmic patients displayed at least one MM-segment as compared to 64% of the non-arrhythmic patients. MMsegments and arrhythmia showed a statistically significant relation (p = 0.018). The logistic regression model predicted the occurrence or absence of arrhythmia in 85% of all cases. Multivariate analysis gave consistent results, after adjusting for symptomatic chronic heart failure (CHF), aneurysms and age. Conclusion: Our results support the hypothesis that hypoperfused but viable myocardium represents an arrhythmogenic substrate and is a relevant risk factor for developing ventricular arrhythmias following myocardial infarction. Therefore, the detection of MM-segments allows the identification of patients with a higher risk for future cardiac events.
Keywords: Viable myocardium; ventricular arrhythmias; post infarction state; 99mTc tetrofosmin SPECT; 18F-FDG PET